Health challenges of the elderly: a comparative study of the need for health social workers in Nigeria and Bangladesh - Adaranijo, Emmanuel Temitope; Hossain, Sarafat (Magyar Gerontológia, 2022)
The established fact is that the population with the highest consumer of healthcare services is the elderly because of the increasing demand for adaptive health services accessible to the elderly. As the elderly continue to age, there is a decline in the health condition, developed societies have explored and employed several multidisciplinary approaches to the care of the elderly. The focus is on social work as a profession.